discussant - Pavoni, A. (URD_SOTA 2023 PHD PROGRAMME IN URBAN AND REGIONAL DEVELOPMENT - State of the art Meeting 2023, 2023)
State of the Art Meeting of the PhD in Urban and Regional Development, Turin Polytechnic